Modeling the Hotel Tax Revenue in Central Lombok using Nonparametric Regression - Nurul Fitriyani; Joji Ardian Pembargi; Ena Setiawana; Rosanti W. ahidatussolihah (Department of Mathematics, Hasanuddin University, 2023)
In Central Lombok Regency, the hotel tax is one of the highest incomes contributing to Regional Original Revenue. A hotel tax is a tax on services provided by the hotel. This research aims to estimate the nonparametric kernel regression curve on hotel tax revenue data in Central Lombok. The method used is nonparametric kernel regression analysis with the seven kernel functions. The results of the analysis with the Generalized Cross Validation (GCV) criteria, the optimal bandwidth values ​​generated by the seven kernel functions have varying values. Although the bandwidth values ​​vary, the resulting estimation results are similar, and the comparison of the Mean Square Error (MSE) values ​​of the seven kernel functions is not significantly different.